2020
DOI: 10.3389/fnins.2020.00051
|View full text |Cite
|
Sign up to set email alerts
|

Functional Integration and Segregation in Multiplex Brain Networks for Alzheimer's Disease

Abstract: Growing evidence links impairment of brain functions in Alzheimer's disease (AD) with disruptions of brain functional connectivity. However, whether the AD brain shows similar changes from a dynamic or cross-frequency view remains poorly explored. This paper provides an effective framework to investigate the properties of multiplex brain networks in AD considering inter-frequency and temporal dynamics. Using resting-state EEG signals, two types of multiplex networks were reconstructed separately considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 59 publications
3
24
1
Order By: Relevance
“…In future works it will be combined with multi-layer network theory, further discussing the correlation between different channels with constructing multi-layer network. In past research we confirmed the feasibility of the multi-layer network scheme, and extracted the multiplex clustering coefficient and multiplex participation coefficient (Cai et al, 2020 ). Future work will consider both the implicit characteristics of single channels and the information integration between multiple channels.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…In future works it will be combined with multi-layer network theory, further discussing the correlation between different channels with constructing multi-layer network. In past research we confirmed the feasibility of the multi-layer network scheme, and extracted the multiplex clustering coefficient and multiplex participation coefficient (Cai et al, 2020 ). Future work will consider both the implicit characteristics of single channels and the information integration between multiple channels.…”
Section: Conclusion and Discussionmentioning
confidence: 58%
“…Currently, more and more scholars adopt the method of detecting dynamic functional connectivity [12,13], which reflects how the functional connectivity of the brain changes over time [14]. Some studies have found that diseases can change the dynamic characteristics of functional connectivity, which can be used as a physiological index for disease research [15], and has important theoretical and practical value for the study of the dynamic characteristics of brain functional networks. Dynamic functional connectivity can more accurately represent the dynamic features of the brain [11], whereas static functional connectivity also helps to understand brain correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the network attempting to maintain synchrony by temporally aligning may then contribute to dysfunction of other nuclei within the basal ganglia 134,135 . Conversely, the response found within the VTA would suggest robustness resilience to cascades of energy usage or pathogens 100,136 .…”
Section: Discussionmentioning
confidence: 99%